2020
DOI: 10.3758/s13423-020-01744-5
|View full text |Cite
|
Sign up to set email alerts
|

A model comparison approach reveals individual variation in the scope and control of attention

Abstract: The maintenance capacity of working memory is known to be severely limited in scope. However, the reason this capacity varies across individuals remains unknown because it has proven difficult to estimate the maximum capacity of an individual's "scope of attention" (SoA) separate from their ability to achieve this maximum capacity due to temporary lapses in "attention control" (AC). The present study accomplished this separation by using a maximum likelihood framework to extract latent constructs representing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…10 Accordingly, both sampling theory and mutualism take a formative rather than a reflective view of g (see Borsboom et al, 2004). 22 control aspects (Hakim et al, 2020;Schor et al, 2020) and some have suggested differentiating attentional consistency and intensity (Unsworth & Miller, 2021). It is conceivable that different tasks may place a larger emphasis on one facet than the other, perhaps consistent with sampling theory.…”
Section: Figure 12mentioning
confidence: 95%
“…10 Accordingly, both sampling theory and mutualism take a formative rather than a reflective view of g (see Borsboom et al, 2004). 22 control aspects (Hakim et al, 2020;Schor et al, 2020) and some have suggested differentiating attentional consistency and intensity (Unsworth & Miller, 2021). It is conceivable that different tasks may place a larger emphasis on one facet than the other, perhaps consistent with sampling theory.…”
Section: Figure 12mentioning
confidence: 95%
“…To calculate the negative log-likelihood, we generated probability distributions at the specific combinations of parameter values via simulation (i.e., synthetic probability distributions). We simulated the number of objects successfully encoded based on a beta-binomial distribution previously demonstrated to explain performance on a WM whole-report task (see partial drop model in Hakim et al, 2020 NGIAM, LOETSCHER, AND AWH 4 and also in Schor et al, 2020Schor et al, , 2023. The beta-binomial distribution estimates the probability of successfully encoding an item from 0 to an individual's maximum capacity, K max .…”
Section: The Object-based Pointer Modelmentioning
confidence: 99%
“…Here, we examined this issue by using a whole-report procedure in which recall for all features of every to-be-remembered item was tested during each trial (Adam et al, 2015(Adam et al, , 2017Hakim et al, 2020;Schor et al, 2020). The key virtue of this approach is that it provides a richer picture of the distribution of successfully stored features across the six items in the memory array.…”
mentioning
confidence: 99%
“…Occasionally, people experience lapses of attention, such as distraction by external or internal information (e.g., mind-wandering). Like most human traits, the capacity of working memory and the ability to control attention are normally distributed in the population (Schor et al, 2020 ). Both working memory capacity and attention control abilities range from weak to strong even in healthy young adults.…”
Section: Introductionmentioning
confidence: 99%